Neuroplasticidad en personas con baja visión: locus preferente retinal y su potencial para la rehabilitación visual - Juricic U., María de los Ángeles; Vilches A., Mayline; Araya C., Javiera; Maldonado A., Pedro; Nazal Ch., Samir (Revista Hospital Clínico Universidad de Chile, 2020)
Visual rehabilitation in people with irreversible Low Vision (LV) aims to optimize the use of remaining vision to execute visual tasks. Conventional rehabilitation exploits the visual potential through training using the remaining visual function, with or without visual aids, to improve performance on specific tasks. However, there is no consensus about the impact of this approach in the long term and on the quality of life of patients. On the other hand, visual neuro-rehabilitation has long-term advantages that can be complementary to conventional strategies and is based on the generation of scotoma awareness and training in the systematic use of extrafoveal regions for fixation and for use as oculomotor reference. These regions called preferred retinal loci (PRL) are established spontaneously in the peripheral retina that still retain visual function and constitute evidence of a high degree of plasticity of the visual system. There is wide evidence of the efficacy of visual neuro-rehabilitation strategies on performance in specific visual tasks, but their impact on the overall visual performance and quality of life of patients is still pending.